CONCEPTUALIZATION OF THE THEORY OF MODERNIZATION IN MODERN POLITICAL SCIENTIFIC RESEARCH - Руденко, Ю. Ю. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2020)
There is a need to distinguish between modernization as a theory and as a process. It is noted that modernization should also be distinguished in a broad sense (as a constant process of producing certain responses to environmental challenges) and in a narrow sense (as a process of learning models of economic, social, political and cultural development of Western society).The content of the theory of modernization as an interdisciplinary system of views, ideas, schemes, and models of analysis is revealed, which reveals the dynamics of overcoming the backwardness of traditional societies, studies the patterns of transformation of transitional societies into modern, developed ones.As a process, modernization is interpreted by modern science as a process of acquisition by less developed societies of a number of features characteristic of more developed societies.     There are several stages in the evolution of the theory of modernization, the features of each of them are considered. The first stage (mid-1950s and 1960s) was the period of the origin and formation of the theory of modernization, the development of concrete-oriented models of socio-economic development based on it. At the second stage of modernization there was a reassessment of the ideas of the first stage, analysis of miscalculations identified in socio-political practice. It has been proved that modernization has an inverse vector. The main element on which the nature of transitional processes and transformations depends, began to be considered a socio-cultural factor. The third, modern, stage of modernization (late 1980s - early 1990s) took place in the context of the collapse of the world socialist system, when post-socialist countries tried to become on a par with developed Western countries through Westernization. There is an error in the mechanical transfer of the Western model to other countries due to disregard for the different potential of their development and the ability of developed countries to constantly improve their system.       It turns out that at the present stage it is worth talking more about "post-modernization", which is based on the desire for deep understanding of various social and political actors in society, the search for new social values, the ability to compromise on fundamental political issues and more.